Fetoscopic laser valve ablation in the posterior urethral valve case with intrauterine diagnosis - Kumru, Selahattin; Kaya, Serdar (Perinatal Journal, 2020)
Objective: We aimed to present the procedure of intrauterine percutaneous fetoscopic laser valve ablation performed on a fetus diagnosed with lower urinary tract obstruction. Case(s): Bilateral hydroureteronephrosis, dilated bladder and oligo/ anhydramnios were found in the fetal ultrasonography examination of a 21-year-old pregnant woman who did not have regular follow-ups, and the lower urinary tract obstruction consistent with the posterior urethral valve was considered in the case. The patient who was found to have poor prognosis as a result of vesico synthesis carried out consecutively was informed about the follow-up and treatment options, and the posterior urethral valve ablation was performed by the percutaneous fetoscopic laser on 27 weeks of gestation. The amniotic fluid was at normal levels after the procedure, and the labor was carried out at term. The newborn with elevated postpartum creatinine was diagnosed with stage 2 renal failure, but dialysis was not required during the follow-ups. The newborn was discharged for outpatient follow-up upon the reduced creatinine levels. Conclusion: By taking the survival enhancing effect of the intrauterine intervention into account in the presence of lower urinary tract obstruction, we considered that intrauterine intervention can be an option in the cases who prefer to continue their pregnancies. The families should be informed in detail about the benefits and risks of intrauterine intervention to repair the obstruction.